Selective oxidation of cyclohexane on a novel catalyst Mg–Cu/SBA-15 by molecular oxygen. Issue 39 (21st September 2015) - Duan, Xiaogang; Liu, Weimin; Yue, Lumin; Fu, Wei; Ha, Minh Ngoc; Li, Jun; Lu, Guanzhong
Abstract : Novel catalysts with copper and magnesium oxide co-supported on mesoporous silica exhibited a special catalytic activity and selectivity for the liquid-phase oxidation of cyclohexane by O2 . Abstract : The novel catalysts x Mg–2.3Cu/SBA-15 with copper and magnesium oxide co-supported on mesoporous silica were synthesized by an impregnation method. The newly synthesized catalysts were characterized using a series of techniques such as BET, XRD, H2 -TPR, UV-vis, XPS, EDS and TEM. The catalytic performance was evaluated by using selective oxidation of cyclohexane with molecular oxygen as the oxidant in a solvent free system. The incorporation of magnesium improved the dispersion of copper oxide and prevented the deep oxidation of cyclohexanol and cyclohexanone. The selectivity of K/A oil was up to 99.3% with 12% conversion of cyclohexane over the 1.2Mg–2.3Cu/SBA-15 catalyst. To our knowledge, this is the best result for the heterogeneous oxidation of cyclohexane by O2 .